2018
DOI: 10.1016/j.ophtha.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Errors & Refractive Surgery Preferred Practice Pattern®

Abstract: for Quality Eye Care without any external financial support. Authors and reviewers of the guidelines are volunteers and do not receive any financial compensation for their contributions to the documents. The guidelines are externally reviewed by experts and stakeholders before publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 687 publications
1
53
0
6
Order By: Relevance
“…90 Due to unstable refractive error associated with hyperglycemia, patients with uncontrolled diabetes have worse refractive outcomes. [91][92][93] Halkiadakis et al reported no significant difference in clinical outcomes for patients with diabetes with good glycemic control undergoing LASIK. 94 The American Academy of Ophthalmology considers uncontrolled diabetes an absolute contraindication, but well-controlled diabetes a relative contraindication for refractive surgery.…”
Section: Corneamentioning
confidence: 99%
“…90 Due to unstable refractive error associated with hyperglycemia, patients with uncontrolled diabetes have worse refractive outcomes. [91][92][93] Halkiadakis et al reported no significant difference in clinical outcomes for patients with diabetes with good glycemic control undergoing LASIK. 94 The American Academy of Ophthalmology considers uncontrolled diabetes an absolute contraindication, but well-controlled diabetes a relative contraindication for refractive surgery.…”
Section: Corneamentioning
confidence: 99%
“…The preoperative evaluation must include monocular manifest refraction, cycloplegic refraction, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), pupillometry, tonometry, anterior chamber depth (ACD) measurement, corneal topography/tomography, pachymetry, aberrometry, tear film quality and quantity, determining the dominant eye, ocular motility, and a fundus examination [18,21]. Cycloplegic refraction is recommended to exclude the accommodation effect, while in patients in/or close to presbyopia age near visual acuity should be checked also.…”
Section: Indications and Preoperative Preparation For Refractive Surgerymentioning
confidence: 99%
“…Cycloplegic refraction is recommended to exclude the accommodation effect, while in patients in/or close to presbyopia age near visual acuity should be checked also. It is mandatory to check the patient's refractive stability during the time, which can most often be obtained by inspecting the patient's eyeglasses or by reviewing the previous ophthalmological documentation [21].…”
Section: Indications and Preoperative Preparation For Refractive Surgerymentioning
confidence: 99%
“…In this paper, these questions are addressed by referring to best clinical practice and adherence to the guidelines for evidence-based practice. [19][20][21]…”
Section: Introductionmentioning
confidence: 99%